FLICKERING SIGNALS: CONTRADICTIONS IN THE JOURNEY OF COMMUNITY TELEVISION STATIONS - Katz, Eliana Miriam; Cohen, David Yitzhak (Ayden Journal of Management and Social Sciences, 2024)
This paper scrutinizes the intriguing trajectory of a widely embraced weekly community television (CTV) program within an Israeli kibbutz during the late 1990s and early 2000s, spotlighting its notable success and its abrupt termination at the apparent zenith of its popularity. Utilizing Social capital theory and deliberation theory as analytical frameworks, this study dissects the intricate web of institutional and individual factors that underlie the fortunes or failures of community media initiatives. Its overarching objective is to enrich our comprehension of how media platforms can foster both social cohesion and democratic governance, and to explore the potential synergy or tension between these dual objectives. Drawing upon the empirical insights gleaned, this research endeavors to distill practical lessons of broader relevance, serving as a guide for the preservation of the dual capacity of community media endeavors as spaces for both deliberative discourse and active community participation.